Textbooks Decontextualization within Bilingual Education in Colombia - Patarroyo Foncesa, Mónica (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Studies about textbooks proposed by authors such as Savignon (1997, 2001); Tomlinson (2003); Núñez, Téllez, Catellanos and Ramos (2009); Ramos and Aguirre (2014), demonstrate that these do not always match the context where English as a Foreign Language (EFL) is being learned. As a consequence, learning English can become arduous and meaningless, i.e., non-natural settings are created to learn the language (Ordóñez, 2011), and textbooks do not prepare learners for real language use (Tomlinson, 2003). In Colombia, English textbooks are included as a means to support language learning under bilingualism policies. However, their authenticity and cultural content are not accurate within the national context. This article presents an overview of the concepts of bilingualism and bilingual education, followed by a discussion concerning the textbooks, as facilitators in learning a language. Some conclusions are also offered regarding the importance of using contextualized materials when learning EFL.